One year monitoring of the Z24-Bridge environmental effects versus damage events. - Peeters, Bart (Earthquake engineering & structural dynamics.)
When using the analysis of vibration measurements as a tool for health monitoring of bridges, the problem arises of separating abnormal changes from normal changes in the dynamic behaviour. Normal changes are caused by varying environmental conditions such as humidity, wind and most important, temperature. The temperature may have an impact on the boundary conditions and the material properties. Abnormal changes on the other hand are caused by a loss of stiffness somewhere along the bridge. It is clear that the normal changes should not raise an alarm in the monitoring system (i.e. a false positive), whereas the abnormal changes may be critical for the structure's safety. In the frame of the European SIMCES project, the Z24 Bridge in Switzerland was monitored during almost one year before it was artificially damaged. Black box models are determined from the healthy bridge data. These models describe the variations of eigenfrequencies as a function of temperature. New data are compared with the models. If an eigenfrequency exceeds certain confidence intervals of the model, there is probably another cause than the temperature that drives the eigenfrequency variations, for instance damage.